2015
DOI: 10.1155/2015/714919
|View full text |Cite
|
Sign up to set email alerts
|

From Eye Drops to ICU, a Case Report of Three Side Effects of Ophthalmic Timolol Maleate in the Same Patient

Abstract: Timolol Maleate (also called Timolol) is a nonselective beta-adrenergic blocker and a class II antiarrhythmic drug, which is used to treat intraocular hypertension. It has been reported to cause systemic side effects especially in elderly patients with other comorbidities. These side effects are due to systemic absorption of the drug and it is known that Timolol is measurable in the serum following ophthalmic use. Chances of life threatening side effects increase if these are coprescribed with other cardiodepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…His condition required intensive care unit admission with mechanical ventilation and temporary transvenous pacing. 21 This emphasises the need to raise awareness among clinicians regarding the potential side effects and drug interactions for timolol.…”
Section: Discussionmentioning
confidence: 99%
“…His condition required intensive care unit admission with mechanical ventilation and temporary transvenous pacing. 21 This emphasises the need to raise awareness among clinicians regarding the potential side effects and drug interactions for timolol.…”
Section: Discussionmentioning
confidence: 99%
“…Its topical ocular preparation is considered amongst the first-line agent for lowering the IOP in patients with POAG, raised IOP secondary to traumatic cataract, and intraocular hypertension (IOH). It was first introduced in 1978 and since then has been used in ophthalmology as a wonder drug, especially in elderly patients, to help with glaucoma [1-2].…”
Section: Discussionmentioning
confidence: 99%
“…Another study published by Rana et al showed three side-effects that were concomitantly present in the patient leading to his demise. These included low blood sugar levels, sinus bradycardia with variable heart block, and orthostatic hypotension [2]. It is also known to cause sick-sinus syndrome and third-degree heart blocks [6].…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of the timolol delivered from an eye-drop collects in the nasolacrimal duct, where it is absorbed through nasal mucosa and enters the bloodstream, reaching a serum concentration of 0.4 ng/mL (∼1.3 nM). 10,11 Because this concentration exceeds the k i for βARs in the heart and lung, it may result in cardiac and respiratory dysfunctions. 7,10,1215 Finally, topical application of 0.5% timolol is also known to induce migraines, burning-sensations, and blurred-vision that collectively undermine medication compliance.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Because this concentration exceeds the k i for βARs in the heart and lung, it may result in cardiac and respiratory dysfunctions. 7,10,1215 Finally, topical application of 0.5% timolol is also known to induce migraines, burning-sensations, and blurred-vision that collectively undermine medication compliance. 8,16 Although drug-soaked contact lenses have been reported to release drugs to manage glaucoma, they offer few benefits over traditional eye-drops because the drug molecules rapidly diffuse out of the lens.…”
Section: Introductionmentioning
confidence: 99%